2019
DOI: 10.1017/s1751731119001915
|View full text |Cite
|
Sign up to set email alerts
|

Review: innovation through research in the North American pork industry

Abstract: This article involved a broad search of applied sciences for milestone technologies we deem to be the most significant innovations applied by the North American pork industry, during the past 10 to 12 years. Several innovations shifted the trajectory of improvement or resolved significant production limitations. Each is being integrated into practice, with the exception being gene editing technology, which is undergoing the federal approval process. Advances in molecular genomics have been applied to gene edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Thus, during the nursing stage, colostrum is a vital source of energy-rich nutrients, maternal antibodies, and growth factors required for glucoregulation and mucosal immune system development, which are needed for piglet survival [50]. Although nursing pigs receive immune protection from their mother, some bacterial and viral pathogens overwhelm this protection (e.g., E. coli), while transboundary pathogens that the mother has not been exposed to (e.g., PEDv) cause nearly 100% piglet death until sows have time to develop immunity which they can pass on via colostral antibodies [1].…”
Section: Production Phase Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, during the nursing stage, colostrum is a vital source of energy-rich nutrients, maternal antibodies, and growth factors required for glucoregulation and mucosal immune system development, which are needed for piglet survival [50]. Although nursing pigs receive immune protection from their mother, some bacterial and viral pathogens overwhelm this protection (e.g., E. coli), while transboundary pathogens that the mother has not been exposed to (e.g., PEDv) cause nearly 100% piglet death until sows have time to develop immunity which they can pass on via colostral antibodies [1].…”
Section: Production Phase Vulnerabilitiesmentioning
confidence: 99%
“…Antibiotics have long been used in the swine industry for therapeutic purposes, as they are in human medicine, to prevent severe clinical disease and death [1]. Antibiotics work against bacteria and different classes of antibiotics have distinct targeting spectrums and potencies [2].…”
Section: Introductionmentioning
confidence: 99%
“… Main et al (2004) reported that as weaning age increased, mortality decreased, day 42 bodyweight increased and weight at harvest reflected greater weight per day of age. In that study, the oldest weaning age was 21 d. Boyd et al (2019) reported that nursery mortality and total mortality to harvest declined as weaning age increased from 18 to 24 d of age, and that the benefit was greater if sow flows were positive for PPRSv and PEDv. McLamb et al (2013) reported that small increases in weaning age, from 16 to 18 to 20 d of age, greatly enhanced the ability of pigs to respond to an ETEC challenge and reduce its physiological and immunological impact.…”
Section: Management Strategies To Improve Abf Productionmentioning
confidence: 91%
“… Li et al (2019) observed that carbohydrase blends reduced markers of gut and systemic inflammation coinciding with improved growth performance in newly weaned pigs. Improved barrier function and reduced systemic and tissue inflammation may explain observations by Boyd et al (2019) that xylanase inclusion in the diet of growing and finishing pigs reduced mortality.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 98%
“…The industry's interest in new technology is perfectly revealed in the report by Boyd et al (2019). They identify innovations which have altered the very trajectory of the industry in North America, and probably globally; this includes the adoption of the tools of molecular genetics to accelerate genetic improvement, molecular-based tools to improve disease diagnosis and control and the tools of near-infrared spectroscopy (NIRS) to improve the precision of feed production (Bjustrom-Kraft et al, 2018;Faba et al, 2019).…”
mentioning
confidence: 99%